2016
DOI: 10.1097/md.0000000000004302
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the effects of remifentanil-based general anesthesia and popliteal nerve block on postoperative pain and hemodynamic stability in diabetic patients undergoing distal foot amputation

Abstract: Diabetic foot ulcer is the most common cause of diabetes-associated nontraumatic lower extremity amputation. Most patients who undergo lower extremity amputation for a diabetic foot have had diabetes for a long time and suffer from multiorgan disorder; thus, it can be a challenge to ensure sufficient anesthetic and analgesic effects while maintaining stable hemodynamics. Recently, peripheral nerve block has gained popularity owing to its attenuating effects of systemic concerns. This retrospective observationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 30 publications
2
20
0
Order By: Relevance
“…The procedure time in our study ranged from 150 to 300 min, which was substantially longer than the duration of, e.g., minor foot amputations performed under RA 30 . Still, the PNB allowed to complete the intervention successfully.…”
Section: Discussionmentioning
confidence: 84%
“…The procedure time in our study ranged from 150 to 300 min, which was substantially longer than the duration of, e.g., minor foot amputations performed under RA 30 . Still, the PNB allowed to complete the intervention successfully.…”
Section: Discussionmentioning
confidence: 84%
“…We could not investigate the effect of larger doses of remifentanil on hemodynamic stability since remifentanil doses were similar between the GA and GA with PNB groups. A previous study found lower mean blood pressures despite larger doses of ephedrine in patients who received remifentanil-based analgesia compared to GA with PNB [11].…”
Section: Discussionmentioning
confidence: 85%
“…Some authors have reported the successful use of PNB for lower extremity amputation patients, in order to avoid the systemic adverse effects of general anesthesia [2,3]. Favorable aspects of PNB, such as better pain control and functional recovery, have been emphasized, although the impact of anesthesia methods on postoperative mortality remains controversial [10][11][12].…”
Section: Discussionmentioning
confidence: 99%
“…First, some experts suggest that the anesthesia effect of deep peroneal nerve innervation can be solved by skin infiltration anesthesia, which can not only reduce the risk of acupuncture but also make anesthesia simpler. However, our literature review suggested that this is not feasible for the following reasons: (1) skin infiltration anesthesia cannot guarantee an ideal anesthesia effect and anesthesia time, while injection of the drug solution into the peripheral nerve can ensure an ideal anesthesia effect [7] .…”
Section: Discussionmentioning
confidence: 99%